Agarwood Induction: Current Developments and Future Perspectives - Tan, Cheng Seng; Isa, Nurulhikma Md; Ismail, Ismanizan; Zainal, Zamri (Frontiers in Plant Science, 2019)
Agarwood is a resinous part of the non-timber Aquilaria tree, which is a highly valuable product for medicine and fragrance purposes. To protect the endangered Aquilaria species, mass plantation of Aquilaria trees has become a sustainable way in Asian countries to obtain the highly valuable agarwood. As only physiologically triggered Aquilaria tree can produce agarwood, effective induction methods are long sought in the agarwood industry. In this paper, we attempt to provide an overview for the past efforts towards the understanding of agarwood formation, the evolvement of induction methods and their further development prospects by integrating it with high-throughput omics approaches.